The Role of Placental Hormones in Mediating Maternal Adaptations to Support Pregnancy and Lactation - Napso, Tina; Yong, Hannah E. J.; Lopez-Tello, Jorge; Sferruzzi-Perri, Amanda N. (Frontiers in Physiology, 2018)
During pregnancy, the mother must adapt her body systems to support nutrient and oxygen supply for growth of the baby in utero and during the subsequent lactation. These include changes in the cardiovascular, pulmonary, immune and metabolic systems of the mother. Failure to appropriately adjust maternal physiology to the pregnant state may result in pregnancy complications, including gestational diabetes and abnormal birth weight, which can further lead to a range of medically significant complications for the mother and baby. The placenta, which forms the functional interface separating the maternal and fetal circulations, is important for mediating adaptations in maternal physiology. It secretes a plethora of hormones into the maternal circulation which modulate her physiology and transfers the oxygen and nutrients available to the fetus for growth. Among these placental hormones, the prolactin-growth hormone family, steroids and neuropeptides play critical roles in driving maternal physiological adaptations during pregnancy. This review examines the changes that occur in maternal physiology in response to pregnancy and the significance of placental hormone production in mediating such changes.